Structural analysis of solid rocket motor with effects of viscoelastic Poisson's ratio. Issue 1 (1st June 2022) - Wang, Junqi; Bao, Futing; Cui, Huiru
Abstract: The new measured viscoelastic Poisson's ratio (VPR) is introduced to investigate the effect of its variation on structure integrity analysis of solid rocket motor. A developed relaxation constitutive model considering VPR is utilized to implement in the finite element code MSC.Marc. Cooling analysis and ignition pressure loading case are designed to analyze the effects along the inner surface of propellant grains. Results show that the little change of the VPR including equilibrium Poisson's ratio (ePR) and reference temperature will affect the output of simulation, and the same up variation of the VPR has relatively less effect on the analysis than the elastic one. Furthermore, the up variation of viscoelastic Poisson ratio will disturb the distribution of strain and stress along the inner surface of propellant grains seriously while the elastic one won't.